Business Performance Achievement At Growth Level - Saddewisasi, Wyati; Widowati, Sri Yuni; Hartoto, Witjaksono Eko (Economics and Business Solutions Journal, 2018)
Mico Small and Medium Enterprises (MSMEs) play a very important role in stability, job creation and economic development of the nation. Thus, MSMEs need to acquire the attention of all parties by paying attention to the potential that exists in each region especially in the era of Asean Economic Community (AEC). This research is generally aimed to describe: MSMEs Strategy in facing AEC. This research uses descriptive explorative approach by analyzing MSMEs strategy in facing AEC. The survey was conducted on five featured clusters of MSMEs in Semarang City namely batik cluster, food processing cluster, handicraft cluster, tourism cluster and milkfish cluster. The population of this study consists of MSMEs entrepreneurs who joined MSMEs clusters in the city of Semarang. Selection of Semarang city as a research location is determined based on the consideration of economic development plan aspect especially in the field of trade. Determination of the MSMEs entrepreneur samples is done purposively based on the consideration of homogeneity and real condition of MSMEs clusters in Semarang City. The number of employer samples is 78 people. Data obtained from the field of research are analyzed descriptively by using Internal-External Matrix model. This study resulted in the conclusion that to face the era of AEC, the appropriate strategies for MSMEs in Semarang city is the strategy of growth through horizontal integration.